A REVIEW ON CARBOFURAN IN THE ENVIRONMENT: PERSISTENCE, TOXICOLOGICAL IMPACTS AND MICROBIAL BIOREMEDIATION STRATEGIES - Ibrahim, Salihu; Mashi Ahmed, Jamila; Bababgana, Kamaluddeen; Atiku, Uwais Muhammad; Yakubu, Kabiru; Babandi, Abba; Ibrahim, Salihu (FUDMA Journal of Sciences, 2026)
Carbofuran is one of the most toxic broad-spectrum and systemic N-methyl carbamate pesticide, which is extensively applied as insecticide, nematicide and acaricide for agricultural, domestic and industrial purposes. It is extremely lethal to mammals, birds, fish and wildlife due to its anticholinesterase activity, which inhibits acetyl-cholinesterase and butyrylcholinesterse activity. In humans, carbofuran is associated with endocrine disrupting activity, reproductive disorders, cytotoxic and genotoxic abnormalities. Therefore, cleanup of carbofuran-contaminated environments is of utmost concern and urgently needs an adequate, advanced and effective remedial technology. Several conventional technologies are used for the removal of carbofuran including physicochemical processing like photo-catalysis, ozonation/UV-irradiation, membrane filtration, adsorption and fenton degradation. However, none of these technologies is feasible and cost effective for complete mineralization of carbofuran pollution from the environment. Microbial technology is a very potent, pragmatic and ecofriendly approach for the removal of carbofuran. Microbial carbofuran degradation provides a safe and cheaper alternative compared to chemical and physical methods. Microbial enzymes and their catabolic genes exhibit an exceptional potential for bioremediation strategies. This study aimed to review the microbial pathways of the biodegradation of carbofuran in agricultural soil to sustainable mitigation of environmental and human health risk. To conduct this review, databases such as Scopus, web of science, PubMed and google scholar were searched to extract studies on the carbofuran biodegradation methods from 2010 to 2025. The role of the isolated bacteria as degrader of carbofuran make it an important instrument for biodegradation of pollutants for sustainable agricultural practices.
Keywords: Carbofuran; Biodegradation; Insecticide; Organocarbamate; Catabolic genes